Immunomodulatory effects of Lactiplantibacillus plantarum CCFM8661 + stachyose on cyclophosphamide-induced immunosuppression mice - Weiwei Ma; Hang Sun; Lian Lian; Lidong Guo; Yanyan Wang; Lili Huang (Frontiers in Immunology)
IntroductionThe increasing stress of modern life has led to a decline in immunity, sparking widespread interest in new strategies to boost immune function. Lactiplantibacillus plantarum and stachyose have gained attention for their immune-regulating effects, but the mechanisms of their combined application remain unclear. This study aims to investigate the immunoregulatory effects of Lactiplantibacillus plantarum CCFM8661 combined with stachyose in cyclophosphamide-induced immunocompromised mice.MethodsMice were divided into the normal control group, model control group (normal saline), positive drug control group (levamisole hydrochloride, 10 mg/kg), and low, medium, and high-dose groups (1.5×105, 1.5×106, and 1.5×107 CFU of Lactiplantibacillus plantarum CCFM8661 + 1.5 mg stachyose). Each treatment group received continuous oral gavage administration for 28 days. On days 23 and 24, except for the normal control group, all other groups were intraperitoneally injected with cyclophosphamide (40 mg/kg) to establish an immunosuppressed model. On day 28, 30 minutes after the final administration, the mice were euthanized to collect the thymus, spleen, serum, ileum, and feces for subsequent analysis of immune indicators, intestinal barrier function, serum cytokines, and intestinal microbiota.ResultsThe combination significantly improved immune organ atrophy, restored intestinal morphology, and normalized cytokine levels in immunosuppressed mice, indicating enhanced immune function. Additionally, it restored intestinal microbiota diversity by increasing the abundance of Muribaculaceae while reducing Lachnospiraceae, potentially promoting intestinal homeostasis.DiscussionThe combination of Lactiplantibacillus plantarum CCFM8661 and stachyose has immune-enhancing effects, potentially achieved by regulating inflammation levels and maintaining intestinal homeostasis.